Геохронологія плагіогранітів "шереметівського" комплексу (Волинський мегаблок Українського щита) - Костенко, О.М.; Довбуш, Т.І.; Степанюк, Л.М. (Мінералогічний журнал, 2011)
За допомогою класичного ізохронного уран-свинцевого методу встановлено час кристалізації цирконів із плагіогранітів шереметівського комплексу, поширених західніше від Коростенського плутону. Вік водяно-прозорих призматичних світло- та коричнювато-рожевих кристалів циркону, відібраних із неелектромагнітної фракції (а, отже, й плагіогранітів), становить 2092,2 ± 3,2 млн рр. Таким чином, за результатами радіо гео хронологічних досліджень встановлено (як і за геологічними даними), що плагіограніти шереметівського комплексу є дещо древнішими за двопольовошпатові гранітоїди житомирського комплексу (2,08 млрд рр.). С помощью классического изохронного уран-свинцового метода установлено время кристаллизации цирконов из плагиогранитов шереметьевского комплекса, развитых западнее Коростенского плутона. Возраст водянисто-прозрачных призматических светло- и коричневато-розовых кристаллов циркона, отобранных из неэлектромагнитной фракции (а, следовательно, и плагиогранитов), составляет 2092,2 ± 3,2 млн лет. Таким образом, в результате радиогеохронологических исследований установлено (как и по геологическим данным), что плагиограниты шереметьевского комплекса несколько древнее двуполевошпатовых гранитоидов житомирского комплекса (2,08 млрд лет). Sheremetiv complex consists of plagiogranites and pla giomigmatites which were formed by the rocks of Vasylivka suite of Teteriv series of Volyn megablock of the Ukrainian Shield. Originally, before plagiogranites and plagio migmatites were distinguished in a single Sheremetiv complex these rocks as well as two-feldspathic granites belonged to Kirovograd-Zhitomir complex, and in a later stratigraphic correlation scale, after the disjoint of Kirovograd-Zhitomir complex, they belonged to Zhitomir complex. The age of accessory zircons from plagiogranites, which are widespread near the village Zoryanka in Emilchino region of Zhitomir province (in the vicinity of western boundary of Korosten pluton) is determined using the classical isochronous uranium-lead method. Plagiogranite is grey, low-medium-grained rock with a parallel arran gement of mineral grains which compose the schistose texture. It consists of plagioclase, quartz, biotite, amphibole that form the granoblastic, and sometimes allo triomorfic or hipidiomorfic-granular texture of the rock. Secon dary chlorite and epidotе are observed in the single grains. Size of the mineral ranged from 0.2 to 2 mm. Morphological features of zircons from plagiogranites are described. The crystals are of prismatic form (from elongate- prismatic with Kelong. = 3—6 to prismatic, Kelong. >2), which are mainly light pink, whereas about 30 % of grains are light brown. Short prismatic (Kelong. = 2.0—1.5) species among low-grained crystals. Partially isotropic shells which grow on light pink kernels similar to the birefringence of light-pink zircons are found inside the brown species. The age of transparent prismatic light pink zircons and pink-brown crystals selected from non-electromagnetic fraction (as well as plagiogranites) is 2092.2 ± 3.2 million years, according to the results of isotopic dating. Thus, using results of geochronology research (as well as geological data) we can assume, that plagiogranites of Sheremetiv complex are older than two-feldspathic granitoids of Zhitomir complex (2.08 billion years).